The Aestheticisation of History in Hussein Arif’s Şar (The City) - Salih, Jutiar Omer; Mohammad, Hama Dler Amin; Arif , Kawan Othman (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
History is so rich in events it can provide many stories and contexts for literary works and contribute to their plots greatly. Literature, in turn, affects history in that when a literary work records an event it adds some elements to it that are not usually found in history books written on the same matter. This is not necessarily changing history but rather literarising and aestheticising it. This happens when a writer decides to present history in a fictionalized manner and rewrites it as literature not as sheer history. There are numerous writers across different nations and time periods to have attempted this such as Leo Tolstoy, Charles Dickens, Fyodor Dostoevsky, Gabriel Garcia Marquez, Najib Mahfouz, Bozorg Alavi, Yashar Kemal etc. One of the best practitioners of this genre in Kurdish literature is Hussein Arif who has used the history of his own country and nation as a basis for his literature. There is much history found in Arif’s many short story collections and three novels. This paper focuses on how Arif has documented several historical events in his first novel called Şar (The City). The setting of this novel, in terms of time, spans sixteen years commencing from 1942. Therefore, the historical events that appear in it date back to the middle decades of the 20th century. The paper first presents the events and discusses them as history then illustrates how Arif has produced aesthetically valuable literature from them. Several extracts are taken from the narrative to show the aesthetic value of the events.